(untitled) (Comentario Internacional: Revista del Centro Andino de Estudios Internacionales, 2011)
Reseña del libro de Paul Collier, The Plundered Planet: Why We Must –and How We Can– Manage Nature for Global Prosperity, New York: Oxford University Press, 2010.